Ginseng-derived Nanoparticles Inhibit Lung Cancer Cell Growth by Promoting Macrophage M1 Polarization - Liangliang FAN; Limei REN; Song YANG; Wenjing LI; Yueming ZHAO; Ronghua ZHAO; Daqing ZHAO; Jiawen WANG (Shipin gongye ke-ji)
Objective: To explore the molecular mechanism by which ginseng-derived nanoparticles (GDNPs) inhibit the growth of human non-small cell lung cancer cells (A549) by altering the polarization state of macrophages. This study will provide a theoretical basis for further research on fresh ginseng medicine. Methods: The CCK-8 assay was employed to detect the effect of GDNPs on the viability of macrophages (RAW264.7). Real-time quantitative PCR was utilized to detect the transcript levels of IL-6, iNOS, TNF-α, and MCP-1, which were indicators related to the M1 polarization of macrophages stimulated by GDNPs. Flow cytometry was utilized to detect the expression of M1 macrophages molecular markers CD80, which was related to the M1 polarization of macrophages stimulated by GDNPs. RAW264.7 cells were treated with LPS and GDNPs, and the culture supernatants were collected to prepare a conditional medium (CM), which was subsequently co-cultured with A549 cells. CCK-8 and flow cytometry were employed to assess the cell viability, cell cycle, and apoptosis of A549 cells. Western blotting was performed to investigate the effect of GDNPs-CM on the expression of TLR4/MyD88 pathway-related proteins in A549 cells. Results: GDNPs enhanced the cell viability of macrophages (P<0.05, P<0.01) and increased the transcript levels of IL-6, iNOS, TNF-α, and MCP-1 (P<0.05, P<0.01, P<0.0001). GDNPs enhanced the the expression of M1 macrophages molecular markers CD80 (P<0.01). Under the influence of GDNPs-CM, the cell viability of A549 cells was inhibited, and the cells exhibited G1 phase arrest with an increased apoptosis rate (P<0.05, P<0.01). Simultaneously, GDNPs-CM promoted the expression levels of inflammation-related proteins, such as TLR4, MyD88, NF-κB, iNOS, and COX-2 in A549 cells (P<0.05, P<0.01). Conclusion: GDNPs induce apoptosis in lung cancer cells by stimulating M1 polarization of macrophages, inhibiting the proliferation of A549 cells, regulating the A549 cell cycle, and activating the TLR4/MyD88/NF-κB signaling pathway to promote the expression levels of inflammatory factors.